2020
DOI: 10.1016/j.amjcard.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Statin Use Prior to Admission to Severity and Recovery Among COVID-19 Inpatients

Abstract: The impact of statins, angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers (ARBs) on coronavirus disease 2019 (COVID-19) severity and recovery is important given their high prevalence of use among individuals at risk for severe COVID-19. We studied the association between use of statin/angiotensin-converting enzyme inhibitors/ARB in the month before hospital admission, with risk of severe outcome, and with time to severe outcome or disease recovery, among patients hospitalized for COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 30 publications
9
142
1
5
Order By: Relevance
“…Several observational studies have evaluated the potential beneficial role of statins in COVID-19 [ [30] , [31] , [32] , [33] , [34] ] ( Table 1 ). Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several observational studies have evaluated the potential beneficial role of statins in COVID-19 [ [30] , [31] , [32] , [33] , [34] ] ( Table 1 ). Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on SARS-CoV-2 identified similar syncytia (Buchrieser et al, 2020;Cattin-Ortolá et al, 2020;Ou et al, 2020;Papa et al, 2020;Xia et al, 2020), which may or may not be relevant to patient pathology (Bryce et al, 2020;Giacca et al, 2020;Rockx et al, 2020;Tian et al, 2020). It remains an open question if syncytia are related to viral and host cell membrane composition, and whether their formation provides mechanistic insights into membrane-targeting therapeutics directed toward enveloped viruses including SARS-CoV-2 (Daniels et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the meta-analysis of these seven studies performed in Western countries are reported in ►Fig. 2, [35][36][37][38][39][40][41] which demonstrate that COVID-19 patients taking statins had nearly 40% lower odds of progressing to the composite endpoint of severe/critical illness or death (OR: 0.59; 95% CI: 0.35-0.99; Cochran's Q p ¼ 0.02; I 2 ¼ 60%). Individually, six of these seven studies reported a reduced OR (i.e., OR < 1; protective effect of statins), [35][36][37][38][39][40] while in only one study was the OR >1 (i.e., OR: 1.60; 95% CI: 0.88-2.92).…”
Section: Resultsmentioning
confidence: 99%